THE ROLE OF 3D MODEL AS SURGICAL GUIDANCE IN MANDIBULAR RECONSTRUCTION SURGERY - Mohammad Adhitya Latief; Benny S Latief; Lilies D S (Jurnal Ilmiah dan Teknologi Kedokteran Gigi, 2020)
reconstruction surgery is a challenging surgery that require well prepared presurgical plan to minimize the risk of failure, to accommodate the need for precision preoperative planning, surgeons frequently need guidance such as a3-dimensional (3D) model to display complex cranial structures. Evaluation of the 3D model as surgical guidance require a review measurement regarding its efficiency and pitfalls. Purpose: the purpose of this research is to understand the importants key points that will resulted succesfull reconstructive surgery using 3D model as surgical guidance. Method:   the evaluation of surgical result in mandibular reconstruction surgery from our Department Oral and Maxillofacial surgery, Universitas Indonesia from 2012 to 2017 reveal the differences. We analyze several keypoints that may affect to the succesfull of reconstruction surgery result. Result: we compared the result between years before and after 2015, this is where we start obligate all reconstruction surgery need to have preoperative planning using3D Model. Several keypoints in using 3D model is acknowledgeable. Conclusion: the use of 3D models as surgical guidance has important role to minimize post reconstructive surgery result, surgeon need to understand the principal and keypoints in preoperative planning and regarding the use of 3D model.